Reductive coupling reactions of organosilanes for the monoselective C–F functionalization of trifluoromethylarenes - Wright, Shawn E., author; Bandar, Jeffrey, advisor; Paton, Robert, committee member; Borch, Thomas, committee member; Herrera-Alonso, Margarita, committee member (Colorado State University. Libraries, 2022)
The mono-selective defluorofunctionalization of trifluoromethylarenes is an emerging strategy to access ⍺,⍺-difluorobenzylic derivatives, which are difficult to access in a divergent manner. Fluorine incorporation is a common strategy employed during the optimization of potential pharmaceuticals in the drug discovery process. Much effort has been spent over the past few decades in developing fluorination methodologies, and the result has been tremendous growth in aryl and alkyl fluorination and trifluoromethylation reactions. On the other hand, methods to install other fluoroalkyl motifs are less developed. Due to the abundant availability of trifluoromethylarenes, mono-selective defluorofunctionalization reactions would be an ideal route to access ⍺,⍺-difluorobenzylic derivatives, which are becoming increasing examined in drug discovery settings. Chapter one will provide the necessary background to understand the context of the work described throughout the following chapters. First, there will be an overview of the importance of fluorine for the development of pharmaceutical compounds. Then there will be a brief summary of the different strategies that have been developed to achieve the trifluoromethylation of arenes as well as the common routes to access ⍺,⍺-difluorobenzylic compounds. Finally, a thorough discussion of the challenges and reported solutions to achieve mono-selective defluorofunctionalization of trifluoromethylarenes will be provided. Chapter two will describe the initial discovery, development, and mechanistic investigation of the defluoroallylation reaction reported by the Bandar group. This discovery led to the identification of a new strategy to achieve reductive coupling through the use of Lewis base activated organosilanes, which provides the basis for the reactions discovered and developed in chapters three and four. Chapter three will describe the discovery, development, and mechanistic investigation of a reductive coupling reaction of trifluoromethylarenes with formamides. This reaction generates a silylated hemiaminal product which is a valuable synthetic intermediate to access a broad scope of ⍺,⍺-difluorobenzylic derivatives. Mechanistic investigations support the generation of a ⍺,⍺-difluorobenzylsilane intermediate in the reaction. Isolated of the ⍺,⍺-difluorobenzylsilane and subsequent derivatizations further broaden the scope of transformations accessible via this reductive coupling process. Chapter four will describe the discovery and preliminary development of the mono-selective hydrodefluorination of trifluoromethylarenes using hydrosilanes activated by a Lewis basic catalyst. Two different catalytic systems are demonstrated that operate via different mechanisms, which provides access to different reaction scopes. A short discussion on the future work of this project will also be provided, where a junior graduate student is developing conditions to enable the mono-selective hydrodefluorination of electron-neutral trifluoromethylarenes.
Keywords: organic synthesis; defluorofunctionalization